COUPLING NORSOK CO2 CORROSION PREDICTION MODEL WITH PIPELINES THERMAL/HYDRAULIC MODELS TO SIMULATE CO2 CORROSION ALONG PIPELINES - Mohyaldinn, Mysara Eissa (School of Engineering. Taylor’s University, 2011)
Pipelines transporting oil and gas are vulnerable to internal corrosion when water forms a part of the transported fluids. The presence of carbon dioxide (CO2) in the fluid accelerates the corrosion rate due to its reaction with water which results in forming carbonic acid, and hence, water pH is reduced. The corrosion rate prediction is an important task needed to manage and control the corrosion. The prediction can be carried on by selecting one of many empirical and mechanistic models that developed for corrosion rate prediction. One of these models is NORSOK model, an empirical model developed by NORSOK Norwegian standard for CO2 corrosion prediction in straight pipes. In this paper NORSOK model has been coupled to thermal and hydraulic models to predict CO2 corrosion rate along pipelines.